Nursing sensitive indicators of structure and outcome in intensive care units - Elaine Machado de Oliveira; Silvia Regina Secoli; Katia Grillo Padilha (Archives of Nursing Practice and Care - Peertechz Publications, 2020)
Objective: To associate the Nursing Sensitive Indicators of structure related to nursing staff with Nursing Sensitive Indicators of outcome in the Intensive Care Units.  Method: Prospective cohort study developed in 8 adult Intensive Care Units, with a sample of patients composed of simple random sampling and nursing professionals composed by 2 categories: nurses and nursing assistants. The nursing workload was measured by the Nursing Activities Score instrument. A linear regression model associated variable of structure and outcome, considering a statistical significance of 5%. Results: The study found 265 patients, 115 nurses and 256 nursing technicians. The length of stay (p<0.05), mean of nurse (p<0.05) and nursing assistant (p<0.05), mean of patient per nurse (p<0.05) were associated with the Nursing Sensitive of outcome. Conclusion: The NSI of structure length of stay, mean of nurse and nursing assistant, and mean of patient per nurse associate with the NSI of outcome in this study.